Prevalence of Hepatitis-D Virus Infection in Hepatitis B Surface Antigen-Positive Children in Southern Punjab (Medical Forum Monthly, 2024)
Background: Hepatitis D virus (H D V) is a defective R N A Virus dependent on Hepatitis B virus ( H B V ) infection for its replication and expression. It is known that co-existent infection with HDV tends to aggravate the course of HBV-associated liver disease. This study was carried out to determine the sero- prevalence of HDV among Hepatitis B Surface antigen (HBSAg) Positive children visiting the Nishtar Medical Centre Jampur (Rajanpur)Study Design: Experimental studyPlace and Duration of Study: This study was carried out at Nishtar Medical Centre Jampur (Rajanpur) from December2010 to September 2012.Materials and Methods: 280 children, out of them 175 were male and 105 were female, having HBSAg Positive and visited the Clinic during the above-said period were included in the study.Results: Effective Preventive measures are the need of hour and Pakistan may be considered as area of highest Prevalence around the globe (JPMA59:434,2009)Conclusion: Some serious steps should be carried out to lower down the Prevalence rate of Hepatitis B in Southern Punjab.